DESENVOLVIMENTO DE APLICATIVO MÓVEL DE APOIO AO CUIDADO DE RECÉM-NASCIDOS - Hammel, Gina de Souza Castro (2023)
Work is part of the Sustainable Development Goals: “Ensure healthy lives and promote well-being for all at all ages”, the Ministry of Health's Research Priorities Agenda: "Development of Technologies and Innovation in Health" and "Maternal and Child Health" and the targets set by the Digital Health Strategy for Brazil 2020-2028. It is also part of the Project “Systematization of care and technological innovation in Nursing”, Thematic Area “Technology and Innovation in Nursing”, contemplated by the CAPES/COFEN Agreement Call 08/2021. Considering that postpartum home care is the best strategy to ensure support for first-time mothers and in order to contribute to a new way of thinking and acting in relation to the experiences of mothers caring for newborns, it is intended to Objectives: to identify in the national and international literature mobile applications to support the care of newborns in home environments; Identify mothers’ perceptions of caring for newborns in a home environment; and to describe the process of developing and validating a mobile application to support the care of newborns in a home environment. Methodological path: The study was systematized in sequential stages, between April/2022 and November/2023, using specific agile technologies and tools, in order to take into account the specificities of each of the objectives previously listed. Work was carried out in cooperation with various areas of institutional knowledge: Nursing, Biomedical Engineering, Information Systems, Design, UFNtv, Innovation Environment. Results: Investigative process showed that the feeling of insecurity and the inability to deal with notions of right and wrong caused most of the mothers enormous discomfort and emotional distress. As it was a unique journey, each mother was responsible for her own decisions, which guided her experiences and existential learning, which were amplified through interaction and the mother-child bond. This highlighted the importance of introducing a digital technology capable of supporting mothers in caring for newborns in a home environment. Called RnNeo, the application developed proved to be reliable, safe and accessible to users from different backgrounds and social contexts. It provides relevant and pertinent guidance on the first care required by newborns in the home environment. Final considerations: Caring for newborns in a home environment requires differentiated attention and a formal or informal support network that takes into account the unique specificities of each woman/mother in the personal, family and social spheres. Therefore, in addition to the social support network, it is important to promote wide-reaching digital technologies. Product and its applicability: The RnNeo App, which was developed and validated, proved to be functional and to have the potential to support parents and caregivers in general in a safe and agile way, thereby minimizing adverse events in newborns in the home environment.